Middle colic vein draining to splenic vein: a rare anatomic variation encountered during a right hemicolectomy. - Chrysikos, Dimosthenis; Sgantzos, Markos; Tsiaoussis, John; Piperos, Theodoros; Varlatzidou, Alexandra; Bonatsos, Vasileios; Theodoropoulos, Panagiotis; Noussios, George; Troupis, Theodore; Papapanagiotou, Ioannis; Mariolis-Sapsakos, Theodoros (J Surg Case Rep, 2018)
Right or subtotal colectomy either open or laparoscopic may be a challenging operation owing to technical difficulties. One of these, is to identify a safe and adequate dissection plane, ligating and dissecting lymph nodes around middle colic vessels. The purpose of this study was to depict a rare anatomic variation of middle colic vein (MCV) draining to splenic vein. We report the case of a 55-year-old male patient, who was subjected to a right hemicolectomy for an adenocarcinoma in the ascending colon. During dissecting the transverse mesocolon from the greater omentum, for complete mesocolic excision (CME), we encountered that the MCV drained in the splenic vein. With respect of this rare anatomic variability, CME was completed without hemorrhage. Our aim is to depict that deep knowledge of MCV anatomy and its variations is of paramount importance to achieve CME and to avoid dangerous or massive bleeding.